The syntax of ellipsis evidence from Dutch dialects - Craenenbroeck, Jeroen van, 1976- (New York ; Oxford : Oxford University Press, 2009)
'The Syntax of Ellipsis' investigates a number of elliptical constructions found in Dutch dialects within the framework of the Minimalist Program. Using two case studies, it argues that both the PF-deletion and the pro-theory of ellipsis are needed to account for the full range of elliptical phenomena attested in natural language.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Dutch language -- Dialects -- Syntax; Dutch language -- Dialects -- Ellipsis